Development and Performance Improvement of an Automated Washing System for a Specified Modulator in the Scale of Industrial Automation - Arthur Silitonga; Dimas Adiputra (President University, 2016)
ABSTRACTAutomation is a solution to improve things in industrial world. The automation itself makes the system able to work automatically and decrease the use of man power. Modulator is a part of conditioner system that was being produced without using automation. The process to produce the modulator consists of a number of steps: loading, cutting, washing, drying, and finishing. In order to wash and to dry the modulator automatically, several industrial components are used as the actuators to execute the process. The industrial components such as water pump, solenoid valve, proximity sensor, and pneumatic cylinder are controlled by a Programmable Logic Controller (PLC). The PLC uses ladder programming language to decide the behavior of the system. A feedback system is applied to the system to get a better performance in terms of process lead time. The performance of the process is better after using the feedback system. The system without feedback has an average lead time of 15.4 s and the system with feedback has an average lead time of 14.7 s.Keywords: automation, modulator, PLC, ladder programming language, feedback, lead time.